PROSES PENGEMBANGAN ORGANISASI KURIKULUM DALAM MENINGKATKAN PENDIDIKAN DI INDONESIA - Aset Sugiana (PEDAGOGIK : JURNAL PENDIDIKAN, 2018)
The Organization of the curriculum is a tool makes it easy to achieve student success in learning learning materials effectively. Teaching and learning activities that take place in the classroom without a clear curriculum will lead students to understand the lessons delivered. Organise the curriculum means choosing objectives are clear and objective and in accordance with the needs and interest of students. The organizational model of the curriculum is a subject approach, combined subjects, broad scope, integrated curriculum, core curriculum, activity curriculum. There are many elements contained in the Organization of the curriculum which could be a reference, ie: (1) the concept of Generalization, (2), (3) skill, and (4) values. There are several criteria in formulating an effective curriculum organization, ie: (1) the scope of the material (scope), (2) b. Sequence (sequance), and (3) c. placement of material (grade placement). Some procedures in reorganizing the curriculum can be through: (1) subjects, (2) patchwork, (3) analysis of activities, (4) social functions, (5) opinion surveys, (6) error studies, and (7) problem analysis teenager.